Measuring the elasticity of electricity demand in South Africa: implications for future demand and supply - Kosiorek, Sebastian (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2018)
A key economic issue for government is the ability to effectively match electricity supply to electricity demand, because of the substantial economic losses in the case of where there is too little supply, or the waste of scarce resources where there is too much supply. In the case of South Africa, this issue, the importance of which was highlighted by the power shortages and associated "rolling blackouts" experience in 2008, has led to the creation of the Integrated Resource Plan (IRP) as a means to decide how energy policy will be developed. Recently, however, the IRP 2010 and its subsequent 2013 and 2016 (draft) updates have been criticised as being too optimistic in regards to their projections of economic growth and electricity demand, making the recommendations in these documents to be flawed. Using monthly data from January 1990 to May 2017, together with Autoregressive Distributed Lag (ARDL) bounds testing for cointegration, this paper measures changes in the elasticity of electricity demand as a result of the massive price hikes over the past decade. Thereafter, the implications of changed electricity as well as possibly lower Gross Domestic Product (GDP) growth in the future for forecasts of possible future demand for electricity are examined. From these revised forecasts, it is possible to make appropriate recommendations in regards to electricity supply policy for South Africa including what possible energy mix is needed as well as the requirements for creating new supply to meet possible future demand. It is concluded that future electricity demand is likely to be much lower than forecast in the IRP 2010 and IRP 2013 documents. The degree of uncertainty in electricity demand growth suggests that large-scale increases in supply capacity taking years to construct, such as coal or nuclear, should be avoided. Small, incremental increases in supply that are able to come on stream swiftly, such as gas, solar and wind power, are likely to be more appropriate for meeting South Africa's future needs.
Keywords: Electric power consumption -- South Africa; Electric power distribution -- South Africa; Electric power production -- South Africa; Electric power failures -- South Africa; Electric utilities -- Law and legislation -- South Africa; Autoregression (Statistics); Renewable energy sources -- South Africa; Energy policy -- South Africa; Integrated Resource Plan